A summary of the available technologies for biodiesel production based on a comparison of different feedstock's properties - Marchetti, Jorge Mario (2012)
Biodiesel production is mainly done by carrying on the transesterification reaction while using refined oil, methanol and a homogeneous base catalyst. When using refined oil, a competition between oil for food and oil for fuel is then presented. Even more, the conventional technology has the disadvantage that the raw material has to be very pure, with no traces of other impurities. Otherwise, undesirable products will be produced decreasing the productivity of the process and making a large amount of waste treatment. Because of this, other technologies appear as possible sources for biodiesel production, mainly from refined oil, but also allowing less pure raw material to be used, such as waste oil, frying oil, soapstocks, and animal fats. In this work, a comparison of all these different raw materials, their physicochemical properties and how they can have an influence, and the magnitude of this phenomenon, in the biodiesel production will be presented and compared. Based on the previous analysis, a short summary of the technological possibilities to produce good quality biodiesel from low price raw material will be discussed with the aim of showing their advantages and disadvantages when using different feedstocks. © 2011 The Institution of Chemical Engineers. Published by Elsevier B.V. All rights reserved.